Splenic Atrophy in Dermatitis Herpetiformis. Issue 5811 (20th May 1972) - Pettit, J. E.; Hoffbrand, A. V.; Seah, P. P.; Fry, Lionel
Abstract : Twenty-four patients with dermatitis herpetiformis were investigated for splenic atrophy by splenic scan and clearance of 51 Cr-labelled heat-damaged red blood cells. Eight of them had definite splenic atrophy. The average splenic cross-sectional area of the remaining 16 with normal clearance times was substantially smaller than normal, suggesting some degree of splenic atrophy. No relationship of splenic hypofunction to intestinal biopsy findings, folate status, reticulin antibody, or treatment with a gluten-free diet or dapsone was evident.